STUDY OF TIDAL INFLUENCE ON FLOODING IN KECAMATAN SELAKAU - Nurhadi, Nurhadi; Gunarto, Danang; Umar, Umar (Jurnal Teknik Sipil, 2023)
Kecamatan Selakau has a considerable risk of flooding, which occurs every year. Because it has a low topography, its location on the coast is undoubtedly greatly influenced by tides and is prone to tidal flooding. In an effort to anticipate and reduce the duration and frequency of rain by arranging the drainage system through technical study activities on drainage channels, especially on the Nyirih River drainage channel, which empties directly into the Selakau River.This research aims to examine the effect of the Selakau River's tides on the Nyirih River's drainage flow and the combination of tides and rainfall on the incidence of flooding in the Nyirih River channel. The research methodology used is the descriptive method. Hydrological analysis using the maximum daily rainfall data from Tebas Station. Then the Nyirih River water level tidal readings and the design discharge data are used in the hydrodynamic model analysis.Based on the analysis results using the HEC-RAS Version 6.1.0 software, the water level elevation from sta is at the highest tide conditions without rain. 0+000 to sta. 1 + 466,682 has exceeded the elevation of the existing channel cross-section so that it experiences inundation with a height of 0.02 m"“0.4 m, and at sta. 1 + 694,439 to sta. 2 + 073.878, the water level is still below the existing cross-sectional elevation of the channel, so no inundation occurs. It shows that there is no effect or increase in water level elevation that occurs for the highest tide combination conditions with rainfall return periods of 2, 5, 10, and 20 years, and it is the same as the highest tide conditions without rain, which experience inundation with a height of 0.02 m-0.4 m. Normalization is inefficient and unsuccessful in decreasing floods since sea tides extensively impact the Nyirih along the river channel.